Floristic-structural composition along an edge gradient in upper montane mixed ombrophilous forest fragment in Santa Catarina Composição florístico-estrutural ao longo de um gradiente de borda em fragmento de floresta ombrófila mista alto-montana em Santa Catarina - Ferreira T.S.* (2016)
© 2016, Universidade Federal de Santa Maria. All rights reserved.The objectives of this study were to characterize the floristic and structure of the tree component in Upper Montane Araucaria Forest fragment and to evaluate the influence of the edge effects on tree species organization, structure, richness and diversity. For this, a total of 50, 10 x 20 m, permanent plots divided in five transects spaced, at least, 100 m from each other, were established in the a forest fragment, located in the municipality of Bom Jardim da Serra, SC. The trees with circumference at breast height (CBH) ≥ 15,7 cm were measured (CBH and total height), identified and classified according to the regeneration guilds. The data were analyzed through the index of importance values (IVI), a NMDS analysis (Nonmetric Multidimensional Scaling), a generalized additive model and simple linear regressions. A total of 1,457 individuals, distributed in 29 families, 43 genera and 55 species were surveyed. The most relative important species was Dicksonia sellowiana Hook. There was no influence of edge effect on tree community organization, structure (average diameter, average height and density) and guilds participation. However, values of diversity, richness and evenness were higher at edge areas. We conclude that part of the variation in values related to tree species diversity in the Upper Montane Araucaria Forest was determined by edge distance.